Implementation of tidal turbines in MIKE 3 and Delft3D models of Pentland Firth & Orkney Waters. (1st October 2017) - Waldman, S.; Bastón, S.; Nemalidinne, R.; Chatzirodou, A.; Venugopal, V.; Side, J.
Abstract: As part of the Terawatt project, two regional-scale hydrodynamic models of the Pentland Firth & Orkney waters were developed using unaltered commercially-available software (MIKE 3 and Delft3D), in order to investigate the suitability of such software for predicting the effects of tidal stream energy development. Realistic scenarios for tidal energy extraction were implemented in each, and the predictions of the models with and without turbines compared. Similar predictions were made of depth-averaged current speed (spatial correlation of R 2 = 0.95 ), but bed stress in one model was more than double that in the other due to the use of different values for bed resistance. The effects of energy extraction are consistent between the models at a regional scale but show considerable local differences. We conclude that these model codes are suitable for broad-scale assessment of the effects of energy extraction but that caution, and more detailed survey data, is required at fine scales. Highlights: Models are built in MIKE 3 & Delft3D with energy extraction without modifying code. The models agree on broad scales, but show discrepancies at fine scales. Suitability of these tools for use by industry & regulators is discussed.